Differential hyperpolarization to substance P and calcitonin gene‐related peptide in smooth muscle versus endothelium of mouse mesenteric artery. (21st October 2021) - Norton, Charles E.; Boerman, Erika M.; Segal, Steven S.
Abstract: Objective: We sought to define how sensory neurotransmitters substance P and calcitonin gene‐related peptide (CGRP) affect membrane potential of vascular smooth muscle and endothelium. Methods: Microelectrodes recorded membrane potential of smooth muscle from pressurized mouse mesenteric arteries (diameter, 150 µm) and in endothelial tubes. Results: Resting potential was similar ( −45 mV) for each cell layer. Substance P hyperpolarized smooth muscle and endothelium −15 mV; smooth muscle hyperpolarization was abolished by endothelial disruption or NO synthase inhibition. Blocking KCa channels (apamin + charybdotoxin) attenuated hyperpolarization in both cell types. CGRP hyperpolarized endothelium and smooth muscle −30 mV; smooth muscle hyperpolarization was independent of endothelium. Blocking KCa channels prevented hyperpolarization to CGRP in endothelium but not smooth muscle. Inhibiting KATP channels with glibenclamide or genetic deletion of KIR 6.1 attenuated hyperpolarization in smooth muscle but not endothelium. Pinacidil (KATP channel agonist) hyperpolarized smooth muscle more than endothelium ( −35 vs. −20 mV). Conclusions: Calcitonin gene‐related peptide elicits greater hyperpolarization than substance P. Substance P hyperpolarizes both cell layers through KCa channels and involves endothelium‐derived NO in smooth muscle. Endothelial hyperpolarization to CGRP requires KCa channels, while KATP channels mediate hyperpolarization in smooth muscle. Differential K + channel activation in smooth muscle and endothelium through sensory neurotransmission may selectively tune mesenteric blood flow.